Perbedaan Olahraga Pagi Dan Malam Terhadap Kualitas Tidur Dan Denyut Nadi Basal - Mayva Garcia, Ardhan Fritzy; Faqihuddin, Ahmad Naufal; Ihsan, Mohammad Arhamul; Wicaksono, Muhammad Febrian Galih; Pamungkas, Radyan Sadewa Atmaja; Jevanicha, Seka Aji; Febriansyah, Wahyu (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2026)
This study aims to determine the difference in the effect of morning and evening exercise on sleep quality and basal heart rate. The research method used an experimental approach with a pretest-posttest control group design. The sample consisted of two groups, namely the morning exercise group (conducted at 6:00 a.m.) and the evening exercise group (conducted at 7:00 p.m.), each consisting of 10 respondents aged 18-40 years with normal health conditions. The sleep quality variable was measured using the Pittsburgh Sleep Quality Index (PSQI), while the basal heart rate was measured using a digital heart rate monitor after waking up. The results of the analysis showed a significant difference between the morning and evening exercise groups in terms of sleep quality (p < 0.05), with morning exercise tending to improve sleep quality more than evening exercise. However, no significant difference was found between the groups in terms of basal heart rate (p > 0.05), even though regular exercise at both times was able to reduce the average basal heart rate of the respondents. In conclusion, the time of exercise affects sleep quality, with morning exercise having a more positive effect. Meanwhile, the effect on basal heart rate does not depend directly on the time of exercise, but rather on the consistency of exercise and the individual's fitness level.